2017
DOI: 10.5262/tndt.2017.1003.12
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Infections in Hemodialysis: An Analysis of 19 Cases

Abstract: OBJECTIVE:Metastatic infection is a rare but serious complication in patients undergoing hemodialysis (HD). In this retrospective study, we aimed to analyze the clinical aspects, responsible microorganisms, treatments, and clinical outcomes in HD patients with metastatic infection MATERIAL and METHODS: Metastatic infection was defined as infection that occurs at a location physically separate from the portal of entry of the bacteria. We identified 21 metastatic infections in 19 HD patients at our hospital from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Although ISD could be a possible cause of dorso-lumbar pain syndrome in HD patients, the lack of specificity of the clinical picture might lead to the underdiagnosis of this condition. The articles in the literature cite a series of ISD cases diagnosed in patients in HD programs, without registering enough patients to increase the statistical relevance of the carried-out studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In the present study, we identified 13 patients with ISD (about 0.6% out of the 2157 dialyzed over the last 10 years), less than the data in the literature [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although ISD could be a possible cause of dorso-lumbar pain syndrome in HD patients, the lack of specificity of the clinical picture might lead to the underdiagnosis of this condition. The articles in the literature cite a series of ISD cases diagnosed in patients in HD programs, without registering enough patients to increase the statistical relevance of the carried-out studies [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In the present study, we identified 13 patients with ISD (about 0.6% out of the 2157 dialyzed over the last 10 years), less than the data in the literature [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic regimen for the HD patients was based on Vancomycin administration (61.53% HD vs. 38.88% non-HD). The choice of Vancomycin in patients with negative cultures was based on the etiology most frequently reported in the literature [ 19 , 38 , 39 , 40 , 43 ]. Vancomycin was used for 2–4 weeks and was later replaced with other anti- staphylococcal agents (Clindamycin, Ciprofloxacin, Amikacin).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations